Low-velocity impact behaviour and failure of stiffened steel plates. (July 2017) - Gruben, G.; Sølvernes, S.; Berstad, T.; Morin, D.; Hopperstad, O.S.; Langseth, M.
Abstract: The behaviour and failure of stiffened steel plates subjected to transverse loading by an indenter is studied in this paper. Low-velocity dynamic and quasi-static tests of stiffened plates with geometry adopted from a typical external deck area on an offshore platform were conducted. The results show that the quasi-static tests provide a good reference for impact loading situations, although they displayed a larger displacement at fracture. Finite element simulations of the steel panel tests were performed, using the elastic-viscoplastic J 2 flow theory and a one-parameter fracture criterion. A relatively fine spatial discretization in the load application area was needed to capture accurately the onset of fracture. In order to locally refine the mesh, a method for automatic mesh refinement based on damage driven h-adaptivity was implemented and evaluated against results obtained with fixed meshes of various element sizes. Highlights: Stiffened steel plates subjected to quasi-static and dynamic transversal loading are presented. The quasi-static tests provide a good reference for impact loading situations. A fine spatial discretization is needed to capture accurately the onset of fracture. A method for automatic mesh refinement is presented and evaluated.